ESTUDO COMPARATIVO ENTRE CONSTRUÇÃO MODULAR E CONSTRUÇÃO CONVENCIONAL (REMUNOM, 2024)
The present work proposes to present a comparative analysis between modular construction systems, formed by prefabricated construction components, and the conventional construction system, composed of structural elements in reinforced concrete and sealing for the production of structural elements of the work. Through qualitative, applied, descriptive, explanatory, bibliographic and documentary research, a brief history of the systems was prepared with a description of each stage of the construction process. In the end, a comparison was established between the systems, exposing their main differences and applications. It was concluded that each construction method has its particularities, with the choice between them depending on the specific needs of each project.